Goodwill accounting in the United Kingdom: The effect of international financial reporting standards - Qasim, Amer (2013)
The accounting treatment of goodwill has been the source of much debate and controversy amongst standard setters and financial report preparers in UK and many other countries. There have been great difficulties in the definition, measurement and subsequent accounting treatment for goodwill. Despite this, goodwill is a significant asset in many companies, whose existence and value are maintained by considerable annual expenditure. Accounting for goodwill changed in the UK in 2005 through the combined effects of the new International Accounting Standards, IFRS 3, Business Combinations, and IAS 36 Impairment of Assets. This paper critically examines, based on the accounting literature and professional standards, the change in accounting treatment for goodwill pursuant to international financial reporting standards (IFRSs) by reference to the UK accounting standards. It critically discusses and compares the former UK and new IFRS policies for goodwill accounting demonstrating the advantages of and arguments against the impairment-only approach to goodwill. It also highlights the sources of managerial discretion in testing goodwill for impairment and provides concluding remarks. Further studies are needed to examine the long-term effects of the impairment only approach to determine whether managers’ opportunistic choices or their incentives to convey their privately held information drive the recognition of goodwill impairments. The paper has implications for financial report prepares and users in highlighting conceptual issues of relevance that will arise in the application of the impairment-only approach to goodwill. It also provides a thorough review of the literature published on the accounting treatment for goodwill in the UK and provides avenues for future research.